Beyond Kimchi and K-Dramas: The Korean Food Phenomenon Among University Students in Malaysia - Raman, Zuraida; Bok, Guat Im (EDUCATUM Journal of Social Sciences, 2024)
Since the airing of Winter Sonata in Malaysia in 2002, the Korean Wave, or Hallyu, has become increasingly popular among Malaysians, especially the younger generation. This study aims to understand the attitudes and perceptions of Malaysian university students towards Korean cuisine and explore the factors motivating their interest in it. The study employed quantitative methods using a survey instrument. The respondents were university students at Universiti Sains Malaysia who had consumed Korean food before. The survey was distributed to students via email and social media and a total of 82 students responded to the survey. The study found that mass media, especially Korean dramas and entertainment, significantly shaped university students' food choices. Environmental factors such as the accessibility and availability of Korean food surrounding the university also affected its popularity. Peers played an important role, while family factors had less influence on the popularity of Korean food. Overall, the findings suggest that Korean cuisine is popular among Malaysian youths due to various factors such as media influence, accessibility, and peer influence. These findings highlight the multifaceted nature of global culture among Malaysian youths. As globalisation continues to fade borders and connect people, the study of the perception and acceptance of foreign cultures and their culinary traditions, especially among youth, becomes increasingly important in understanding the intricacy of cultural exchange.